1990
DOI: 10.1037/0022-3514.58.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for terror management theory II: The effects of mortality salience on reactions to those who threaten or bolster the cultural worldview.

Abstract: Three experiments were conducted to test the hypothesis, derived from terror management theory, that reminding people of their mortality increases attraction to those who consensually validate their beliefs and decreases attraction to those who threaten their beliefs. In Study 1, subjects with a Christian religious background were asked to form impressions of Christian and Jewish target persons. Before doing so, mortality was made salient to half of the subjects. In support of predictions, mortality salience l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,132
7
20

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,188 publications
(1,219 citation statements)
references
References 23 publications
35
1,132
7
20
Order By: Relevance
“…That is, reminders of death should lead to strong negative evaluations of persons whose behaviors or beliefs impinge on the cultural worldview, and lead to strong positive evaluations of persons who uphold or bolster the worldview. A more elaborate introduction to terror management theory and the supporting empirical findings is beyond the scope of the current paper, (for more complete descriptions, see e.g., Arndt et al, 1999;Greenberg et al, 1990;Harmon-Jones et al, 1997;Pyszczynski et al, 1999;Rosenblatt et al 1989;Solomon et al, 1991), but it should be noted here that results are in agreement with the theory's line of reasoning.…”
Section: How Fairness Judgments Are Formed: a Closer Look At The Selfmentioning
confidence: 66%
“…That is, reminders of death should lead to strong negative evaluations of persons whose behaviors or beliefs impinge on the cultural worldview, and lead to strong positive evaluations of persons who uphold or bolster the worldview. A more elaborate introduction to terror management theory and the supporting empirical findings is beyond the scope of the current paper, (for more complete descriptions, see e.g., Arndt et al, 1999;Greenberg et al, 1990;Harmon-Jones et al, 1997;Pyszczynski et al, 1999;Rosenblatt et al 1989;Solomon et al, 1991), but it should be noted here that results are in agreement with the theory's line of reasoning.…”
Section: How Fairness Judgments Are Formed: a Closer Look At The Selfmentioning
confidence: 66%
“…Additionally, studies have confirmed that when people are made aware of the inevitability of death, they express greater attraction to those who praise their cultural worldview and decreased attraction to those who criticize the cultural worldview (Greenberg, Pyszczynski, Solomon, Rosenblatt, Veeder, Kirkland, & Lyon, 1990;Dechesne, Janssen, & van Knippenberg, 2000).…”
Section: 実験社会心理学研究 第52巻 第 1号mentioning
confidence: 97%
“…28 People tend to become more dogmatic and tenacious in their belief systems when reminded of their mortality (terror management theory). 29 And under extreme stress, as during a car crash, rape, or battlefield injury, people may dissociate, that is, experience the episode as if from a distance, temporarily protected from pain and awareness of consequences (traumatic stress theory). 30 For such reasons, the Air Force interrogator said he tried to interview terrorist suspects "before any heavy handed ex-Turkish farmer slapped them around."…”
Section: Torturersmentioning
confidence: 99%